Perception of the benefits of the ownership of companion animals in people with fertility disorders - Hugues H., Beatriz (2015)
The aim of this study was to evaluate the perception of persons with fertility disorders regarding pet ownership and its relationship with personal satisfaction and benefits on psicoemotional health. A survey using a questionnaire was conducted. The results showed that 50 and 20% of the persons had dogs and cats as pets respectively. The 88% of persons were very satisfied living with pets. Also, 92% pointed out that their pets provided company and well-being, 87% indicated that felt free of tensions, and 85% mentioned that pets constituted a motive to take better care of themselves. It is concluded that the studied sector perceived personal satisfaction and better emotional health due to pet ownership.